Complex Assessment of X-ray Diffraction in Crystals with Face-Centered Silicon Carbide Lattice; Crystals; Vol. 13, iss. 3 - Bosikov I. I. Igor Ivanovich; Martyushev N. V. Nikita Vladimirovich; Klyuev R. V. Roman Vladimirovich; Tynchenko V. S. Vadim Sergeevich; Kukartsev V. A. Viktor Alekseevich; Eremeeva S. V. Svetlana Vladimirovna; Karlina A. I. Antonina Igorevna (2023, 2023)
Title screen